Management Of Fusarium Solani (Root Rot Of Common Bean) Using Disparate Methodologies - Ndifon, Elias Mjaika (Universitas Andalas, 2023)
Purpose: Common bean is frequently infected by several pathogens which reduce its yield (20–100%) and quality of the produce. Three sub-trials were employed to proffer solutions to infection of beans by Fusarium solani.Methods: All three sub-trials (botanical, chemical, and bio-control sub-trials) were setup using the completely randomized design with each treatment replicated thrice in vitro.Findings: The results of applying synthetic fungicides (i.e.; metalxyl, metalaxyl+copper, and metalaxyl+carboxin) revealed that all the fungicides were significantly different (P≤0.05) compared with the control. Metalaxyl (single agent) was significantly (P≤0.05) less effective compared to combined formulations with metaxyl and other agents. The best treatment was Metalaxyl+Copper (100% concentration) followed by Metalaxyl+Copper (50% concentration), then Metalaxyl+Carboxin (100% concentration), Metalaxyl+Carboxin (50% concentration) in descending order of performance. All the plant extracts (Silk cotton (Ceiba pentandra), Tamarind (Tamarindus indica), wild cardamom (Sulettaria surculosa), and Eucalyptus (Eucalyptus globolus)) were significantly different (P≤0.05) compared with the control. The highest control of this pathogen was attained using Eucalyptus (100% concentration), followed by Eucalyptus (50% concentration), Cardamom (100% concentration), Cardamom (50% concentration), Silk cotton (100% concentration), Tamarind (100% concentration), Tamarind (50% concentration), and finally Silk cotton (50% concentration). The inhibitory efficacy of Trichoderma isolates shows that they were significantly different (P≤0.05) compared with the control. Trichoderma harzianum isolate AIM22 and Trichoderma hamatum isolate ZXPB provided the best control followed by Trichoderma harzianum isolate AIBN, and finally, Trichoderma viride isolate AIBK.Conclusion: The use of these botanical, chemical, and bio-control agents revealed their potency in managing Fusarium solani.